Validity of the recovery-stress questionnaire - Tibbert, S.; Morris, T.; Andersen, M. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Coaches and athletes have long sought the optimum level of training and the most effective ways to handle the demands of repeated competitive performances. A substantial proportion of elite athletes (around 40%) report overtraining (Kenta et al., 2001), Gould et al. (1999) and athletes interviewed from 4 US Olympic teams frequently cited overtraining as a cause of failure. Recently, researchers have shifted the conceptualisation of training and competition demands from overtraining, which focused on physical, pschological, and performance decrements resulting from intensive training to stress-recovery imbalance (SRI), which acknowledges that appropriate recovery can moderate the impact of heavy training. To measure SRI, Kellman and Kallus (2001) developed the Recovery-Stress Questionnaire for Athletes (RESTQ-SPORT). This instrument measures general stress, general recovery, sport-specific stress, and sport-specific recovery. The RESTQ-SPORT has passed standard psychometric validation, but there are few independent tests of its construct validity. The aim of this study was to examine the construct validity of the RESTQ-SPORT by comparing scores of elite athletes in a period of intensive training and competition (HI-INT), with their scores during a less intensive phase (LO-INT). We predicted means for stress subscales would be significantly lower and means for the recovery subscales would be significantly higher for the LO-INT, than for the HI-INT occasion.